Cognitive training with casual video games: points to consider - Baniqued, Pauline L.; Kranz, Michael B.; Voss, Michelle W.; Lee, Hyunkyu; Cosman, Joshua D.; Severson, Joan; Kramer, Arthur F. (Frontiers in Psychology, 2014)
Brain training programs have proliferated in recent years, with claims that video games or computer-based tasks can broadly enhance cognitive function. However, benefits are commonly seen only in trained tasks. Assessing generalized improvement and practicality of laboratory exercises complicate interpretation and application of findings. In this study, we addressed these issues by using active control groups, training tasks that more closely resemble real-world demands and multiple tests to determine transfer of training. We examined whether casual video games can broadly improve cognition and selected training games from a study of the relationship between game performance and cognitive abilities. A total of 209 young adults were randomized into a working memory-reasoning group, an adaptive working memory-reasoning group, an active control game group, and a no-contact control group. Before and after 15 hours of training, participants completed tests of reasoning, working memory, attention, episodic memory, perceptual speed, and self-report measures of executive function, game experience, perceived improvement, knowledge of brain training research, and game play outside the laboratory. Participants improved on the training games, but transfer to untrained tasks was limited. No group showed gains in reasoning, working memory, episodic memory or perceptual speed, but the working memory-reasoning groups improved in divided attention, with better performance in an attention-demanding game, a decreased attentional blink and smaller trail-making costs. Perceived improvements did not differ across training groups and those with low reasoning ability at baseline showed larger gains. Although there are important caveats, our study sheds light on the mixed effects in the training and transfer literature and offers a novel and potentially practical training approach. Still, more research is needed to determine the real-world benefits of computer programs such as casual games.